Analisis Trend Peresepan Golongan Antipsikotika Tipikal dan Atipikal di Tiga Puskesmas di Kota Banjarmasin Periode 2019-2021: Trend Analysis of Prescribing Typical and Atypical Antipsychotics at Three Health Centers in Banjarmasin City for the 2019-2021 Period - Nur Annisa Meilina; Noor Cahaya; Aditya Maulana Perdana Putra (Jurnal Sains dan Kesehatan, 2022)
Antipsychotics are the first-line treatment option for schizophrenia, with the goal of reducing symptoms and preventing relapse. The study aimed to identify and analyze changes in the pattern of use of antipsychotics in prescribing schizophrenia patients based on the category of drug name, class, and dosage form from 2019 to 2021 at 3 primary health care centers in Banjarmasin. The study was designed as a descriptive study, with data collected retrospectively and using a purposive sampling technique based on inclusion and exclusion criteria. A total of 154 samples were analyzed. The results showed a change in the frequency of use of antipsychotics based on the category of drug names, i.e., haloperidol, chlorpromazine, trifluperazine, clozapine, and risperidone; data on the use of the typical antipsychotic group continued to increase compared to the atypical group; and there was no change in the form of prescribing antipsychotics in tablet form. As a result, it was concluded that there is a shift in the use of antipsychotics through prescribing in schizophrenia patients, as evidenced by a change in the percentage of use of both drug items and antipsychotic groups at the 3 primary care health centers from 2019 to 2021.